Investigation into the Reasons for Secondary School Dropouts in Iceland - Seepersad, Austin S (Scholarly Commons, 2018)
The purpose of this investigation is to examine different facets of Iceland’s culture to determine the reasons for its high secondary schools' dropout rates. This study deconstructs what factors in a Nordic society affect academic performance. Reviewing literature on the subject yielded potential factors such as childhood health and parental behaviors, Iceland’s abundance of accessible jobs, and the low accessibility for higher education in rural parts of Iceland. A limited number of personal interviews and firsthand observations indicated that most secondary school dropouts were due to a lack of family support and incentive – especially for male students, due to the type of unskilled labor available.